Detection of Pb(II) and Cr(III) Using Dy(III) Ion with Pyrazoline Derivatives Ligand - Syahputri, Yulian; Sutanto; M. Daud Mahmudin; Mohammad Rommy Izha Ramadhan (Sains Natural: Journal of Biology and Chemistry, 2024)
Exposure to heavy metal ions Pb2+ and Cr3+ in Indonesia is getting more attention, especially in various industries and transportation. The sensor complex compound Dy3+ with fluorescence-based pyrazoline-derived ligands (fluorosensor) has the potential to detect heavy metal ions Pb2+ and Cr2+. This research was initiated by synthesizing the pyrazoline derivative ligand and then reacting it with Dy3+ metal ion.  The formed Dy3+ complex compounds was then characterized using spectroscopic methods. The results of scanning complex compounds using a UV-Vis spectrophotometer obtained two maximum wavelengths namely at 255 and 359 nm are indicating the presence of a transition type n→π* and π→π*. The results of fluorescence spectrophotometer analysis obtained maximum fluorescence intensity of Dy3+ complex compound was in the wavelength at 370 nm with fluorescence intensity of 4273 a.u. Fluorescence based sensor studies of the Dy complex when Pb2+ and Cr3+ metal ions were added showed changes in fluorescence intensity so that the fluorosensor type was obtained for the Dy3+ metal ion complex compound with Pb2+ and Cr3+, namely "turn-on-off" and "turn-off" respectively.